Chitosan beads for the delivery of salmon calcitonin: Preparation and release characteristics - (:unkn) unknown (ELSEVIER SCIENCE BV, 1996)
Salmon calcitonin (sCT)-loaded chitosan beads were prepared by dropping a drug containing solution of chitosan into tripolyphosphate solution. The droplets instantaneously formed gelled spheres by ionotropic gelation. The mean diameter of beads was about 0.9 mm and encapsulation efficiency of drug was 54-59%. The drug was successfully encapsulated at pH 6. The amount of sCT did not affect the drug release from beads. Release data were examined kinetically and the mechanism was discussed. These results show that sCT-loaded chitosan beads could be prepared providing a controlled release property.
Keywords: salmon calcitonin; chitosan; controlled-release; chitosan-polyelectroylte complex